2015
DOI: 10.1292/jvms.14-0624
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal transmission and phylogenetic analysis of bovine leukemia virus in two districts of Miyazaki, Japan

Abstract: Horizontal transmission is recognized as a major infection route for bovine leukemia virus (BLV), and cattle with high viral loads are considered to be a major infectious source in a herd. However, a correlation between viral loads and the risk of infection has been insufficient to use as a foundation for BLV control strategies. In this report, we examined the epidemiology of BLV infection and the infectious source in a local area. In 2013–2014, BLV infection was investigated in 1,823 cattle from 117 farms in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 25 publications
(31 reference statements)
3
32
0
Order By: Relevance
“…Although the mechanism is not clear, the infectiousness of a BLV-infected cow likely corresponds to PVL (Rodríguez et al, 2011). This is supported by studies in both Japan (Mekata et al, 2015) and Argentina (Juliarena et al, 2016), which found that cows with a low PVL were unlikely to spread BLV to herd mates. As well, removal of cattle with high BLV antigen expression reduced the incidence of new BLV infections in an Australian dairy herd (Molloy et al, 1994), and Gutiérrez et al (2014) reported that dams with high PVL were more likely to transmit BLV to their calves.…”
Section: Introductionmentioning
confidence: 92%
“…Although the mechanism is not clear, the infectiousness of a BLV-infected cow likely corresponds to PVL (Rodríguez et al, 2011). This is supported by studies in both Japan (Mekata et al, 2015) and Argentina (Juliarena et al, 2016), which found that cows with a low PVL were unlikely to spread BLV to herd mates. As well, removal of cattle with high BLV antigen expression reduced the incidence of new BLV infections in an Australian dairy herd (Molloy et al, 1994), and Gutiérrez et al (2014) reported that dams with high PVL were more likely to transmit BLV to their calves.…”
Section: Introductionmentioning
confidence: 92%
“…To examine whether the expression levels of viral genes gp51, G4, and R3 are increased by PGE 2 signaling, the PBMCs of BLV-infected cattle were incubated in the presence of PGE 2 (1 mM; Cayman Chemical, Ann Arbor, MI), EP2 agonist [1 mg/ml, Butaprost (free acid), Cayman Chemical] or EP4 agonist (1 mg/ml, Rivenprost; Cayman Chemical) at 37˚C under 5% CO 2 for 3 d and collected, and the expression levels were quantified by qPCR as described above. To measure the proviral loads of samples from BLV-infected cattle, qPCR was performed as previously described, with slight modifications (27). Briefly, genomic DNA was extracted from the PBMCs of BLV-infected cattle using the Wizard Genomic DNA Purification Kit (Promega, Madison, WI).…”
Section: Qpcrmentioning
confidence: 99%
“…genotypes in one herd (Ababneh et al 2012;Mekata et al 2015) . Genotypes 1 and 3 are circulating in specialized dairy farms in Antioquia, since there is no limitation for viral transmission .…”
mentioning
confidence: 99%
“…Genotypes 1 and 3 are circulating in specialized dairy farms in Antioquia, since there is no limitation for viral transmission . Recently the viral load has been linked to horizontal transmission because a cow infected with less than 3 copies of the virus per 100 cells cannot spread BLV to other cattle of more than 30 months old(Mekata et al 2015) . Transmission of the virus can be vertical and horizontal .…”
mentioning
confidence: 99%